Characterization of Guaraguaçú River (Paraná, Brazil) based on the distribution of foraminiferal and thecamoebian assemblages and sedimentological analysis - Pupo, Daniel Vicente; Disaró, Sibelle Trevisan (Anuário do Instituto de Geociências, 2006)
Abstract